REAKSI PASAR MODAL TERHADAP PERISTIWA STOCK SPLIT PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Robert Jao (PROGRESS, 2014)
This study aims to determine whether there are significant differences between the abnormal returns before and after the stock split as well as whether there are significant differences between trading volume activity before and after the stock split.The research was conducted on 29 companies listed in Indonesian Stock Exchange that the stock-split in 2011-2013. This study uses analysis Paired Sample T Test and Wilcoxon Sign RankTest with the observation period (event window) is 31 days which is t=-15 (15 days before the stock split), t=0(the event date) and t=15 (15 days after stock split).The study states that the first hypothesis is nosignificant difference between the abnormal returns before and after the stock split. While the second hypothesis is suggests that there are significant differences between trading volume activity before and after the stock split.